Magnetic code disc material, angular displacement magnetic sensor, high-speed motorized spindle of numerical control machine tool and preparation method of high-speed motorized spindle
By using metal substrate, TA buffer layer, Fecocr to match TAN low -dimensional magnetic thin film and TA protective layer, it solves the problem of density density in the existing technology, and achieves higher magnetic poles. Density and better precision have improved the precision of the processing of CNC machine tools.
Patent Information
- Application Number
- CN202411553044.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-28
AI Technical Summary
The existing magnetic code disk materials have defects such as deterioration in the density of magnetic rings, cavity, and pores in the application of high-speed electric spindles of CNC machine tools, resulting in low signal density and uniformity of angular displacement magnetic sensors, affecting precision positioning.
The magnetic code disk material composed of metal substrate, TA buffer layer, Fecocr is clamped into TAN low -dimensional magnetic thin film and TA protective layer. It is prepared through DC sputtering and vacuum annealing process to form a dual -disk material with excellent magnetic characteristics.
Improve the magnetic pole density and magnetic uniformity, increase the stubborn force and the remaining magnetic properties, avoid the signal matching problem, significantly improve the precision of the corner transposition magnetic sensor, thereby improving the precision of the processing of CNC machine tools.
Smart Images

Figure CN119372601A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of magnetic materials and sensor technology, and specifically relates to a magnetic code disk material, an angular displacement magnetic sensor, a high-speed electric spindle for a CNC machine tool, and a preparation method thereof. Background Art
[0002] CNC machine tools are called "the mother of industry" and "the heart of modern industry". Their technical level is one of the standards for measuring a country's core manufacturing capabilities. Ultra-high precision CNC machine tools require precise positioning during the processing process, so high-precision position sensors are crucial to the motion control system of CNC machine tools; Angular displacement sensors are an indispensable sensor among high-precision position sensors. Angular displacement sensors can be classified into angular displacement grating sensors, angular displacement magnetic sensors, angular displacement capacitive sensors, etc.
[0003] Considering the actual application scenarios of CNC machine tools, their electric spindles still need to maintain extremely high angular accuracy and stability in high-speed application environments of thousands or even tens of thousands of revolutions. Therefore, high-precision angular displacement magnetic sensors are usually used to ensure their reliability; the angular displacement magnetic sensor is composed of a magnetic code disk and a magnetic sensor, and the magnetic code disk needs to use magnetic materials with high magnetic properties and high uniformity, so as to perform high-density encoding on it to ensure signal accuracy.
[0004] The magnetic code disk materials in the prior art are usually made of magnetic powder particles through mold injection molding. The particles are often unevenly distributed, resulting in poor density of the magnetic ring, and even defects such as voids and pores, which make the ferrite material have a lower number of magnetic poles that can be recorded, resulting in low density and uniformity of its magnetic pole signal, and even problems with signal matching of angular displacement magnetic sensors. Therefore, it is necessary to prepare a new high-performance magnetic code disk material to address the current problems that need to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to solve the deficiencies of the prior art and provide a magnetic code disk material, an angular displacement magnetic sensor, a high-speed electric spindle for CNC machine tools and a preparation method thereof, which specifically adopts the following technical solutions:
[0006] A magnetic code disk material comprises, from bottom to top, a metal substrate, a Ta buffer layer, a FeCoCr sandwich TaN low-dimensional magnetic film, and a Ta protective layer; the structure of the FeCoCr sandwich TaN low-dimensional magnetic film is, from bottom to top: a first FeCoCr magnetic layer, a TaN core layer, and a second FeCoCr magnetic layer.
[0007] Preferably, the thickness of the Ta buffer layer is 15nm-25nm, and the thickness of the Ta protective layer is 5nm-10nm.
[0008] Preferably, in the FeCoCr-TaN low-dimensional magnetic film, the thickness of the first FeCoCr magnetic layer is 70nm-110nm, the thickness of the second FeCoCr magnetic layer is 80nm-120nm, and the thickness of the TaN core layer is 10nm-30nm.
[0009] Preferably, the mass ratio of Fe, Co and Cr in the first FeCoCr magnetic layer is (40-44): (25-30): (20-30); the mass ratio of Fe, Co and Cr in the second FeCoCr magnetic layer is (25-41): (32-35): (19-24).
[0010] The present invention also provides a method for preparing the above-mentioned magnetic code disk material, comprising the following steps: using a non-magnetic metal substrate as a metal substrate, performing DC sputtering on the metal substrate, and then performing vacuum annealing to obtain the magnetic code disk material; the DC sputtering includes the following processes: performing a first DC sputtering on the metal substrate to prepare the Ta buffer layer, then performing a second DC sputtering to prepare the first FeCoCr magnetic layer, then performing a third DC sputtering to prepare the TaN core layer, then performing a fourth DC sputtering to prepare the second FeCoCr magnetic layer, and then performing a fifth DC sputtering to prepare the Ta protective layer.
[0011] Preferably, the vacuum degree during the DC sputtering preparation process is 3×10 -5 Pa-4×10 -5 Pa; the first DC sputtering time is 200s-300s, the second DC sputtering time is 1750s-2500s; the third DC sputtering time is 750s-850s; the fourth DC sputtering time is 1800s-2200s; the fifth DC sputtering time is 60s-200s.
[0012] Preferably, the vacuum annealing conditions are: temperature 645°C-655°C, annealing time 25min-35min, and vacuum degree of annealing environment 3×10 -5 Pa-5×10 -5 Pa.
[0013] The present invention also provides an angular displacement magnetic sensor made of the magnetic code disk material.
[0014] Preferably, the angular displacement magnetic sensor has 512 AB phase magnetizing poles with a width of 0.4 mm and 1 Z phase magnetizing pole with a width of 0.4 mm, and the Z phase does not diffuse.
[0015] The present invention also provides a high-speed electric spindle for a numerically controlled machine tool using the angular displacement magnetic sensor.
[0016] The beneficial effects of the present invention are:
[0017] By constructing a magnetic code disk material with a FeCoCr sandwiched TaN low-dimensional magnetic film structure, it has excellent consistency and magnetic uniformity, greatly improved magnetic pole density, smaller magnetic domain size, excellent coercive force and residual magnetic properties, and can provide better magnetic pole density when applied to angular displacement magnetic sensors, so that the signal density is higher. On this basis, through the precisely designed matching structure of the AB phase and the Z phase of the magnetic sensor, the problem of excessive width of the signal acquisition pulse caused by the divergence of single magnetic pole magnetization can be effectively avoided, so that the angular displacement magnetic sensor made of the magnetic code disk material provided by the present invention has better precision, so that when applied to the high-speed electric spindle of CNC machine tools, the precision of CNC machine tools can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Shown is a schematic structural diagram of an angular displacement magnetic sensor supported by the magnetic code disk material provided by the present application;
[0019] Figure 2 The figure shows a comparison diagram of the AB phase and Z phase output signals of the angular displacement magnetic sensor of the prior art and the technical solution provided by the present invention;
[0020] Figure 3 The figure shows the principle diagram of the angular displacement magnetic sensor made of the magnetic code disk material provided by the present invention during the operation of the high-speed electric spindle of a CNC machine tool. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments and drawings to clearly and completely describe the concept, specific structure and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0022] The present invention provides a magnetic code disk material, which has the following structure: a metal substrate, a Ta buffer layer on the metal substrate, a FeCoCr-sandwiched TaN low-dimensional magnetic film on the Ta buffer layer, and a Ta protective layer on the FeCoCr-sandwiched TaN low-dimensional magnetic film; the structure of the FeCoCr-sandwiched TaN low-dimensional magnetic film is: a bottom layer is a first FeCoCr magnetic layer, a TaN core layer is on the first FeCoCr magnetic layer, and a second FeCoCr magnetic layer is on the TaN core layer.
[0023] Example 1
[0024] (1) 316 non-magnetic stainless steel code disc was selected as the metal substrate material. In a magnetron sputtering device, a DC sputtering method was used to deposit the code disc on a 3×10-5 Under the vacuum degree of Pa, a Ta buffer layer was deposited on the substrate with a sputtering power of 50w, a deposition time of 266s, and a thickness of 20nm.
[0025] (2) Using the DC sputtering method, the power is 80W, at 3×10 -5 Under the vacuum degree of Pa, FeCoCr target with a mass ratio of Fe, Co and Cr of 40:25:30 was selected to deposit a FeCoCr nanofilm layer on the Ta buffer layer as the first FeCoCr magnetic layer, with a deposition time of 2045s and a thickness of 100nm.
[0026] (3) Using the DC sputtering method, 3×10 -5 Under a vacuum degree of Pa, a TaN core layer was further deposited on the first FeCoCr magnetic layer for 806 s with a thickness of 20 nm.
[0027] (4) Using the DC sputtering method, the power is 80W, at 3×10 -5 Under the vacuum degree of Pa, FeCoCr target with a mass ratio of Fe, Co and Cr of 41:32:24 was selected, and a FeCoCr nanofilm layer was further deposited on the TaN intermediate layer as the second Fe CoCr magnetic layer, with a deposition time of 2045s and a thickness of 100nm;
[0028] (5) Using the DC sputtering method, at 3×10 -5 Under the vacuum degree of Pa, a Ta protective layer was further deposited on the FeCoCr layer, with a deposition time of 66.6 s, a sputtering power of 50 W, and a thickness of 5 nm.
[0029] (6) After the deposition step is completed, the material obtained in step S5 is subjected to vacuum annealing. The annealing temperature is 645°C, the annealing time is 30 min, and the vacuum degree of the annealing environment is 5×10 -5 Pa.
[0030] After annealing, a magnetic code disk material containing FeCoCr sandwiched TaN low-dimensional magnetic film is obtained, whose coercive force is better than 750Oe and remanence is better than 0.35T.
[0031] Figure 1 As a schematic diagram of the structure of the AB phase and the Z phase of the angular displacement sensor, the preparation method is as follows:
[0032] The outer surface of the magnetic code disk provided by the present invention is divided into two annular outer surfaces as an upper circle and a lower circle. The selected Z-phase position in the lower circle is machined to cut out a convex structure with a width of 0.4 mm. Subsequently, the upper circle part is magnetized using a magnetizer, and 512 magnetic poles with a width of 0.4 mm are written as alternatingly distributed AB phases. The 0.4 mm convex structure of the lower circle is magnetized to make it a Z phase.
[0033] Figure 1 (a) shows the processing method of the Z phase. The convex part between the two planes cut out is the Z phase, and its processing range is limited to the lower circle position. Figure 1 (b) shows the structure of the magnetized AB phase and Z phase, where the upper circle with densely arranged magnetic poles in a ring is the staggered AB phase, and the lower circle with single magnetic poles is the Z phase.
[0034] Since the Z phase is an outward convex structure and the magnetic code disk material provided by the present invention is used, the Z phase made of the magnetized outward protruding structure with a width of 0.4 mm will not have magnetic signal diffusion, so that the Z phase can be consistent with the AB phase signal, avoiding the positioning deviation caused by a Z phase magnetic signal crossing multiple AB phases due to the diffusion of the Z phase magnetic signal, and effectively avoiding the problem of the signal acquisition Z phase pulse being too wide due to the divergence of single magnetic pole magnetization.
[0035] The schematic diagram of the comparison of the AB phase and Z phase output signals of the angular displacement magnetic sensor is as follows Figure 2 As shown, (a) is a Z-phase signal obtained by using the structural design made of the magnetic code disk material provided by this patent, and its width is consistent with the AB-phase width, avoiding the positioning recognition error caused by a Z-phase signal spanning multiple AB-phase signals; while in (b) as the prior art, a Z-phase signal width spans multiple AB-phase signals, which can easily lead to spindle positioning recognition errors and may even cause the machine tool to not return to zero during processing, which may lead to tool breakage and other phenomena.
[0036] The high-speed electric spindle of a CNC machine tool adopts the above-mentioned angular displacement magnetic sensor, wherein the schematic diagram of the working principle of the angular displacement magnetic sensor is as follows: Figure 3As shown, when the high-speed electric spindle of the CNC machine tool is working, the magnetic drum of the angular displacement sensor is driven to rotate, and the magnetic poles outside the magnetic drum carry the magnetic poles to rotate during the rotation process. The magnetic poles sweep across the surface of the magnetic sensing element of the head reader chip during the rotation process, and the data recorded in the magnetic poles are read by the head reader chip, and the electrical signal is transmitted to the control system of the CNC machine tool through the amplification circuit, thereby determining the working state of the high-speed electric spindle of the CNC machine tool and performing precise control. Among them, since the angular displacement magnetic sensor made of the magnetic code disk material provided by the present invention has a smaller magnetic domain size, higher magnetic signal density, and better uniformity, the magnetic pole spacing on the surface of the angular displacement magnetic sensor is greatly reduced; and the AB phase magnetization magnetic poles reach 512, and the width is only 0.4mm; the Z phase magnetization magnetic pole is 1, the width is 0.4mm, and the Z phase does not diffuse; further, the performance of the angular displacement magnetic sensor prepared by the magnetic code disk material provided by the present application is greatly improved, so that the working state of the high-speed electric spindle of the CNC machine tool can be precisely, accurately, and timely transmitted to the machine tool control device, which significantly improves the processing precision of the CNC machine tool.
[0037] Example 2
[0038] (1) 316 non-magnetic stainless steel code disc was selected as the metal substrate material. In a magnetron sputtering device, a DC sputtering method was used to deposit the code disc on a 4×10 -5 Under a vacuum degree of Pa, a Ta buffer layer was deposited on the substrate with a sputtering power of 50 W, a deposition time of 200 s, and a thickness of 15 nm.
[0039] (2) Using the DC sputtering method, the power is 80W, at 4×10 -5 Under the vacuum degree of Pa, FeCoCr target with a mass ratio of Fe, Co and Cr of 42:28:25 was selected to deposit a FeCoCr nanofilm layer on the Ta buffer layer as the first FeCoCr magnetic layer, with a deposition time of 1432s and a thickness of 70nm.
[0040] (3) Using the DC sputtering method, at 4×10 -5 Under a vacuum degree of Pa, a TaN core layer was further deposited on the first FeCoCr magnetic layer for 806 s with a thickness of 20 nm.
[0041] (4) Using the DC sputtering method, the power is 80W, at 3×10 -5 Under the vacuum degree of Pa, FeCoCr target with a mass ratio of Fe, Co and Cr of 35:35:20 was selected, and a FeCoCr nanofilm layer was further deposited on the TaN intermediate layer as the second Fe CoCr magnetic layer, with a deposition time of 2352s and a thickness of 115nm.
[0042] (5) Using the DC sputtering method, at 4×10 -5Under the vacuum degree of Pa, a Ta protective layer was further deposited on the FeCoCr layer with a sputtering power of 50 W, a deposition time of 100 s, and a thickness of 7.5 nm.
[0043] (6) After the deposition step is completed, the material obtained in step S5 is subjected to vacuum annealing. The annealing temperature is 655°C, the annealing time is 25 min, and the vacuum degree of the annealing environment is 3×10 -5 Pa.
[0044] After annealing, a magnetic code disk material containing FeCoCr sandwiched TaN low-dimensional magnetic film is obtained, whose coercive force is better than 750Oe and remanence is better than 0.35T.
[0045] Example 3
[0046] (1) 316 non-magnetic stainless steel code disc was selected as the metal substrate material. In a magnetron sputtering device, a DC sputtering method was used to deposit the code disc on a 3×10 -5 Under a vacuum degree of Pa, a Ta buffer layer was deposited on the substrate with a sputtering power of 50 W, a deposition time of 200 s, and a thickness of 15 nm.
[0047] (2) Using the DC sputtering method, the power is 80W, at 3×10 -5 Under the vacuum degree of Pa, FeCoCr target with a mass ratio of Fe, Co and Cr of 44:30:20 was selected to deposit a FeCoCr nanofilm layer on the Ta buffer layer as the first FeCoCr magnetic layer, with a deposition time of 2045s and a thickness of 100nm.
[0048] (3) Using the DC sputtering method, 3×10 -5 Under a vacuum degree of Pa, a TaN core layer was further deposited on the first FeCoCr magnetic layer for 806 s with a thickness of 20 nm.
[0049] (4) Using the DC sputtering method, the power is 80W, at 3×10 -5 Under the vacuum degree of Pa, FeCoCr target with a mass ratio of Fe, Co and Cr of 41:32:24 was selected, and a FeCoCr nanofilm layer was further deposited on the TaN intermediate layer as the second Fe CoCr magnetic layer, with a deposition time of 2454s and a thickness of 120nm.
[0050] (5) Using the DC sputtering method, at 3×10 -5 Under the vacuum degree of Pa, a Ta protective layer was further deposited on the FeCoCr layer with a sputtering power of 50 W, a deposition time of 66.6 s, and a thickness of 5 nm.
[0051] (6) After the deposition step is completed, the material obtained in step S5 is subjected to vacuum annealing. The annealing temperature is 650°C, the annealing time is 35 min, and the vacuum degree of the annealing environment is 4×10 -5 Pa.
[0052] After annealing, a magnetic code disk material containing FeCoCr sandwiched TaN low-dimensional magnetic film is obtained, whose coercive force is better than 750Oe and remanence is better than 0.35T.
[0053] Although the description of the present invention has been quite detailed and has been particularly described with respect to several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, but should be regarded as the intended scope of the invention by reference. In addition, the above description of the present invention is based on the embodiments foreseeable by the inventors, and its purpose is to provide a useful description, and those non-substantial changes to the present invention that have not yet been foreseen may still represent equivalent changes of the present invention.
Claims
1. A magnetic code disk material, characterized in that: The magnetic code disk material includes a metal substrate, a Ta buffer layer, a FeCoCr sandwich TaN low-dimensional magnetic film, and a Ta protective layer from bottom to top; the structure of the FeCoCr sandwich TaN low-dimensional magnetic film is from bottom to top: a first FeCoCr magnetic layer, a TaN core layer, and a second FeCoCr magnetic layer.
2. A magnetic code disk material according to claim 1, characterized in that: The thickness of the Ta buffer layer is 15nm-25nm, and the thickness of the Ta protection layer is 5nm-10nm.
3. A magnetic code disk material according to claim 1, characterized in that: In the FeCoCr-sandwiched TaN low-dimensional magnetic film, the thickness of the first FeCoCr magnetic layer is 70nm-110nm, the thickness of the second FeCoCr magnetic layer is 80nm-120nm, and the thickness of the TaN core layer is 10nm-30nm.
4. A magnetic code disk material according to claim 1, characterized in that: The mass ratio of Fe, Co and Cr in the first FeCoCr magnetic layer is (40-44): (25-30): (20-30); the mass ratio of Fe, Co and Cr in the second FeCoCr magnetic layer is (25-41): (32-35): (19-24).
5. A method for preparing a magnetic code disk material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Using a non-magnetic metal substrate as a metal substrate, performing DC sputtering on the metal substrate, and then performing vacuum annealing to obtain the magnetic code disk material; The DC sputtering includes the following process: performing a first DC sputtering on the metal substrate to prepare the Ta buffer layer, then performing a second DC sputtering to prepare the first FeCoCr magnetic layer, then performing a third DC sputtering to prepare the TaN core layer, then performing a fourth DC sputtering to prepare the second FeCoCr magnetic layer, and then performing a fifth DC sputtering to prepare the Ta protective layer.
6. The method for preparing a magnetic code disk material according to claim 5, characterized in that: The vacuum degree in the DC sputtering process is 3×10 -5 Pa-4×10 -5 Pa; the first DC sputtering time is 200s-300s, the second DC sputtering time is 1750s-2500s; the third DC sputtering time is 750s-850s; the fourth DC sputtering time is 1800s-2200s; the fifth DC sputtering time is 60s-200s.
7. The method for preparing a magnetic code disk material according to claim 5, characterized in that: The vacuum annealing conditions are as follows: temperature 645°C-655°C, annealing time 25min-35min, vacuum degree of annealing environment 3×10 -5 Pa-5×10 -5 Pa.
8. An angular displacement magnetic sensor, characterized in that: The magnetic code disk material comprises any one of claims 1 to 4, or the magnetic code disk material prepared by the preparation method of any one of claims 5 to 7.
9. The angular displacement magnetic sensor according to claim 8, characterized in that: The angular displacement magnetic sensor has 512 AB phase magnetizing poles with a width of 0.4 mm and one Z phase magnetizing pole with a width of 0.4 mm, and the Z phase does not diffuse.
10. A high-speed electric spindle for a CNC machine tool, characterized in that: The magnetic code disk material comprises any one of claims 1 to 4, or the angular displacement magnetic sensor comprises claim 8 or 9.
Citation Information
Cited By
Magnetic code disc material and preparation method thereof, and magnetic encoder
CN119900002A
A magnetic code disk material, a preparation method thereof, and a magnetic encoder
CN119900002B
Absolute value magnetic position sensor and reading method
CN121207224A